2022
DOI: 10.1039/d1mo00398d
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific association of oxidative stress and immune response in septic shock mortality using NMR-based metabolomics

Abstract: Background: Sepsis and septic shock are still associated with a high mortality rate. Early-stage prediction of septic shock outcomes would be helpful to clinicians for designing their treatment protocol. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…The criteria used for generating the final list of significant metabolites were VIP (variable importance of projection) score >1, Boneferrroni-corrected p-value <0.05, and FDR < 0.05. 27 The VIP score measures the significance of each variable in the projection used in the OPLS-DA model. The p-value is the probability that in the study, the observed effect has occurred by chance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The criteria used for generating the final list of significant metabolites were VIP (variable importance of projection) score >1, Boneferrroni-corrected p-value <0.05, and FDR < 0.05. 27 The VIP score measures the significance of each variable in the projection used in the OPLS-DA model. The p-value is the probability that in the study, the observed effect has occurred by chance.…”
Section: Discussionmentioning
confidence: 99%
“…57 Isobutyric acid, a short-chain saturated fatty acid and a product of protein catabolism, is elevated in kidney injury and is considered an organ failure-related metabolite that affects patients. 20,27,58 Valine, a marker for increased severity of ARDS, indicates a shift from the usual energy production pathways to alternative resources. It is a product of muscle breakdown and is expected in patients with acute lung injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Works by Pandey et al illustrated the metabolic alteration in patients with sepsis and septic shock due to the presence of comorbid conditions like diabetes and hypertension 98 , gender 99 , and alteration in metabolic profile during disease or progression of the disease 100 , 101 .…”
Section: Metabolomicsmentioning
confidence: 99%